1983
DOI: 10.1128/jvi.45.1.27-35.1983
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Temperature-Sensitive Cap (m 7 GpppNm)-Dependent Endonuclease

Abstract: The first step in influenza viral mRNA synthesis is the endonucleolytic cleavage of heterologous RNAs containing cap 1 (m 7 GpppNm) structures to generate capped primers that are 10 to 13 nucleotides long, which are then elongated to form the viral mRNA chains. We examined the temperature sensitivity of these steps in vitro by using two WSN virus temperature-sensitive mutants, ts 1 and ts 6, which have a defect in the genome RNA segment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…This is similar to the optimum temperature of the polymerase of influenza C, which is 33°C [62,63]. Ulmanen et al [64] found that the rate of transcription by detergent-treated WSN viruses (influenza A) was about 10 times greater at 33°C than at 39.5°C, and also that the binding of a cleaved primer cap (the ''A13 fragment") to the viral cores was ''unexpectedly" much weaker at 39.5°C than at 33°C. Scholtissek and Rott [65] showed that the optimum for the polymerase of the Rostock strain of fowl plague virus was 36°C, five degrees below chickens' normal body temperature (41°C).…”
Section: The Temperature Sensitivity Of Viral Transcriptionmentioning
confidence: 56%
See 2 more Smart Citations
“…This is similar to the optimum temperature of the polymerase of influenza C, which is 33°C [62,63]. Ulmanen et al [64] found that the rate of transcription by detergent-treated WSN viruses (influenza A) was about 10 times greater at 33°C than at 39.5°C, and also that the binding of a cleaved primer cap (the ''A13 fragment") to the viral cores was ''unexpectedly" much weaker at 39.5°C than at 33°C. Scholtissek and Rott [65] showed that the optimum for the polymerase of the Rostock strain of fowl plague virus was 36°C, five degrees below chickens' normal body temperature (41°C).…”
Section: The Temperature Sensitivity Of Viral Transcriptionmentioning
confidence: 56%
“…There is extensive biochemical evidence for the temperature sensitivity in respiratory viruses, particularly influenza, which is discussed below. This includes temperature sensitivity that is associated with the steps of the uptake of virions into cells [60], RNA transcription [61][62][63][64][65] (including the ts control of the balance between the synthesis of mRNA and replicative products [66,67]), and the transport to the cell surface of hemagglutininesterase-fusion protein, the protein that promotes the fusion of influenza C virions with cells [68].…”
Section: M4: Chilling Increases the Activity Of Respiratory Viruses Amentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to manipulate temperature because high temperature often constitutes a significant stress for viruses (probably due to the lower thermostability of their simple viral proteins) but not their hosts (e.g. Ulmanen et al 1983). We created a gradually, rather than abruptly, degrading thermal environment to maximize biological reality (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, activation by cleavage of a dinucleotide containing one toxic nucleoside has been suggested as a way to utilize viral nucleases as targets for antiviral drugs . Inhibition of the cap dependent endonuclease activity of influenza virus (Ulmanen et al, 1983) should constitute a logical point of attack for an antiviral drug and prevent the utilization of the cellular mRNA cap by the viral polymerase.…”
Section: Degradation Of Nucleotides and Polynucleotidesmentioning
confidence: 99%